2012
DOI: 10.3748/wjg.v18.i45.6620
|View full text |Cite
|
Sign up to set email alerts
|

Value of adipokines in predicting the severity of acute pancreatitis: Comprehensive review

Abstract: High levels of adipokines could allow for prediction of a severe disease course and outcome even in small pancreatic lesions on computed tomography scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Resistin and visfatin were found to be good predictors of pancreatic necrosis with cut-off levels of 11.9 ng/mL and 1.8 ng/mL, respectively. However, Al-Maramhy et al did not find resistin as a useful marker for predicting severity [ 106 , 107 ].…”
Section: Biomarkers Of Pancreatic Necrosismentioning
confidence: 99%
“…Resistin and visfatin were found to be good predictors of pancreatic necrosis with cut-off levels of 11.9 ng/mL and 1.8 ng/mL, respectively. However, Al-Maramhy et al did not find resistin as a useful marker for predicting severity [ 106 , 107 ].…”
Section: Biomarkers Of Pancreatic Necrosismentioning
confidence: 99%
“…These results suggest that the increased leptin concentration in diabetic dogs might have been caused by concurrent diseases, instead of being a direct effect of hyperglycemia due to DM. Previous studies have also provided evidence of the dysregulation of serum leptin concentrations by other specific diseases [ 3 6 17 ]. A recent study of dogs with pituitary-dependent hyperadrenocorticism suggested that higher circulating leptin concentrations might be associated with hypercortisolemia [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of dogs with pituitary-dependent hyperadrenocorticism suggested that higher circulating leptin concentrations might be associated with hypercortisolemia [ 6 ]. In humans, several studies have shown that leptin concentrations were higher in patients with acute pancreatitis [ 17 ] and chronic kidney disease [ 3 ]. In the present study, AP (8/11, 72.7%), HAC (5/11, 45.5%), and CKD (5/11, 45.5%) were confirmed as concurrent disorders in diabetic dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Fat necrosis promotes high level infiltration of leukocytes into damaged areas of adipose tissue, and adipocytes, adipose tissue macrophages, and recruited immune cells become sources of inflammatory cytokines . In human medicine, it has been suggested that increases in the levels of circulating adipokines, especially resistin and visfatin, could be used as specific markers for peripancreatic fat necrosis . However, little information is available about the circulating adipokine concentrations during the pathogenesis of AP in dogs.…”
mentioning
confidence: 99%
“…11 In human medicine, it has been suggested that increases in the levels of circulating adipokines, especially resistin and visfatin, could be used as specific markers for peripancreatic fat necrosis. 12,13 However, little information is available about the circulating adipokine concentrations during the pathogenesis of AP in dogs. In our preliminary study, we measured the adipokine concentrations in dogs with AP, a but the group sizes were small and it was difficult to reach any firm conclusions about the roles of adipokines during the development of AP in dogs.…”
mentioning
confidence: 99%